Loneliness and pain among community-dwelling middle-aged and older Black, Latino, and White adults in the United States - Camacho, David; Burnette, Denise; Aranda, Maria P.; Moxley, Jerad H.; Lukens, Ellen P.; Reid, M. Carrington; Wethington, Elaine (Frontiers in Public Health, 2024)
Background: Prior research has demonstrated a strong and independent association between loneliness and pain, but few studies to date have explored this relationship in racially and ethnically diverse groups of midlife and older adults. We drew on the diathesis stress model of chronic pain and cumulative inequality theory to examine the relationship of loneliness and the presence and intensity of pain in a nationally representative sample of Black, Latino, and White adults aged 50 or older in the United States.Methods: Data were from Wave 3 of the National Social Life, Health, and Aging Project (n = 2,706). We used weighted logistic and ordinary least squares regression analyses to explore main and interactive effects of loneliness and race and ethnicity while adjusting for well-documented risk and protective factors (e.g., educational attainment, perceived relative income, inadequate health insurance, perceived discrimination) and salient social and health factors.Results: Almost half (46%) of the participants reported feeling lonely and 70% reported the presence of pain. Among those who reported pain (n = 1,910), the mean intensity score was 2.89 (range = 1-6) and 22% reported severe or stronger pain. Greater loneliness was associated with increased odds of pain presence[(AOR = 1.154, 95% CI [1.072, 1.242]) and higher pain intensity (β = .039, p < .01). We found no significant interaction effects involving Black participants.However, Latino participants who reported greater loneliness had significantly higher levels of pain (β = .187, p < .001) than their White counterparts with similar levels of loneliness.Discussion: Loneliness is an important correlate of pain presence and intensity and may have a stronger effect on pain intensity among Latino adults aged 50 or older. We discuss clinical and research implications of these findings, including the need for more fine-grained analyses of different types of loneliness (e.g., social, emotional, existential) and their impact on these and other pain-related outcomes (e.g., interference). Our findings suggest a need for interventions to prevent and manage pain by targeting loneliness among middle-aged and older adults, particularly Latino persons.